Effects of acute caffeine intake on muscular power during resistance exercise: a systematic review and meta-analysis - Xiao, Yuchun; Ding, Li; Xu, Zhenbo; Liu, Jue; Guo, Li; Barnes, Matthew J.; Cao, Yinhang; Girard, Olivier (Frontiers in Nutrition, 2025)
BackgroundThis study examined the effects of caffeine on movement velocity and power output during resistance exercises and explored moderating factors influencing these effects.MethodsA systematic search of five databases was conducted through June 2025. A random-effects model was used to assess the effect of caffeine on muscular power-related variables, such as bar velocity and power output, during resistance exercises with a fixed number of repetitions. Subgroup analyses were performed based on sex, caffeine dose, habitual caffeine consumption, muscle group, and load.ResultsTwelve studies comprising 230 participants were included. Caffeine significantly improved mean velocity (SMD = 0.42, 95% CI: 0.19–0.65, p < 0.05, I2 = 85%) and mean power output (SMD = 0.21, 95% CI: 0.12–0.30, p < 0.05, I2 = 14%) during resistance exercises. Greater improvements in mean velocity were observed in males (SMD: 0.56 vs. 0.22), and habitual caffeine consumption < 3 mg/kg/day (SMD: 0.87 vs. 0.21) (all p < 0.01 for subgroup comparisons). Furthermore, although caffeine increased mean velocity at all caffeine doses (SMD: 0.31–0.78), muscle groups (SMD: 0.32–0.54) and loads (SMD: 0.37–0.49) (all p < 0.01), no significant differences were observed between subgroups (all p > 0.01 for subgroup comparison).ConclusionCaffeine ingestion enhances movement velocity and power output during resistance exercises, regardless of load. These benefits were more pronounced in males, at higher caffeine doses, among low habitual caffeine consumers, and during lower-body exercises.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024616920.